Dawn of the light dragon - West, Tracey, 1965-; Loveridge, Matt (2023)
To prevent the Shadow Dragon from plunging the world into sky-shadow the Drake and Darma seek out a Light Dragon named Lysa, but they learn from her dragon master they need to summon a Star Dragon with a star flute, hidden within a dangerous labyrinth.
Ages 6-8
Grades 2-3
Keywords: Dragons -- Juvenile fiction; Magic -- Juvenile fiction; Wizards -- Juvenile fiction; Labyrinths -- Juvenile fiction; Adventure stories; Dragons -- Fiction; Magic -- Fiction; Wizards -- Fiction; Labyrinths -- Fiction; Adventure and adventurers -- Fiction; Action and adventure fiction; Fantasy fiction